Nutritional status, literacy, and risk factors of malnutrition in the population over 50 years of age - findings from the SHARE project - Tereza Vágnerová; Olga Dvořáčková; Eva Topinková (Clinical Nutrition Open Science, 2024)
Summary: Background & Aims: The transition from middle age to old age (from adults aged 50–55 years to older seniors aged 75–80 years) represents a critical period in terms of changes in body composition, i.e., increase in body fat percentage and decrease in fat-free body mass, which occur even at long-term stable weight. These changes are caused, among other things, by a gradual reduction in physical activity and deterioration in dietary habits. For many health conditions, like weight status, nutritional assessment and nutritional literacy can provide valuable information that can guide treatment efforts and maintenance of healthy eating habits. We therefore attempted to map this issue using data from the Survey of Health, Ageing and Retirement in Europe (SHARE) project. Methods: The basis for this study was data from the 8th wave of the SHARE project. The analysis included the results of the primary questionnaires CAPI (Computer Assisted Personal Interviewing) and the National Dropoff Questionnaire developed exclusively for the Czech Republic with a special module D “Nutrition” summarizing questions on eating habits, nutrition care and nutritional literacy. Results: A total of 2316 respondents were included in the study, 37.9% of whom were female and 62.1% male, with a mean age of 71.7±7.6 years. The prevalence of undernutrition, overweight and obesity in the study population was 9.2%, 42.8% and 32.2%, respectively. The presence of depression, anxiety, polypharmacy, multimorbidity and pain were associated with poor nutritional status (Pearson correlation coefficient, P < 0.001 for all five factors). The lifestyle factors of dietary habits and regular physical activity of the subjects did not meet current recommendations. Awareness of the existence and availability of dietitians and the possibilities of nutritional therapy and its reimbursement from public health insurance proved to be low. Conclusion: The results show a high prevalence of overweight, obesity and malnutrition in the Czech population over 50 years of age, low nutritional literacy, and inadequate coverage of nutritional care.